On the nature of the fine structure in emission spectra of XeCl laser - Blonskyy, I.V.; Gnatovskyy, A.V.; Zubrilin, N.G.; Pavlov, I.A.; Chernomorets, M.P. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2004)
Results of investigation of the fine structure existing in emission spectra of the transverse-discharge pumped XeCl laser are presented. Influence of selective components of the cavity on the structure of spectrum of induced emission is investigated. Conditions of manifestation in the emission spectra of fine structure caused by the molecules rotation are clarified. Generation frequencies in the region of 0–3 transition are measured.